High-density genetic map construction using whole-genome resequencing of the Cymbidium eburneum(‘Duzhan Chun’) × Cymbidium insigne (‘Meihua Lan’) F1 population and localization of flower color genes - Han, Yu; Cui, Yutong; Chen, Yu; Rao, Dandan; Wu, Erhuan; Gan, Rongcun; Li, Tengmin; Tian, Mi (Frontiers in Plant Science, 2025)
As a traditional and valuable ornamental flower in China, Cymbidium orchids exhibit significant developmental potential in the floriculture industry due to their profound cultural connotations and unique aesthetic characteristics. Flower color diversity, as one of the most important ornamental traits, not only attracts extensive attention in the breeding and development of new varieties but also plays a critical role in the evolution of floral traits and ecological functions. Color changes during the flowering process of Cymbidium are common; however, the genetic regulatory networks underlying these dynamics remain insufficiently understood. In this study, an F1 hybrid population consisting of 150 individuals derived from a cross between Cymbidium goeringii (‘Duzhan Chun’) and Cymbidium insigne (‘Meihua Lan’) was employed. Using whole-genome resequencing at an average depth of 5×, a high-density genetic linkage map was constructed. The sequencing data exhibited excellent quality (Q30 ≥ 96%), and after stringent quality control, 2,306,434 high-quality SNPs were retained. Ultimately, a genetic map comprising 7,734 bin markers was established, spanning a total genetic distance of 255.945 cM with an average marker interval of 1.19 cM. Genome-wide association study (GWAS) identified 121 SNP loci significantly associated with flower color (P < 1 × 10⁻5), which were predominantly enriched in carotenoid biosynthesis and phenylpropanoid metabolic pathways. Candidate gene analysis revealed that 9-cis-epoxycarotenoid dioxygenase (NCED), the MYB60 transcription factor, carotene epsilon-monooxygenase (LUT1), and the WRKY6 transcription factor likely influence flower color formation by regulating pigment synthesis and accumulation. This study not only establishes the highest-density genetic linkage map for Cymbidium to date but also systematically elucidates the genetic basis of flower color variation, providing critical theoretical foundations and molecular marker resources for molecular breeding in Cymbidium.